2014
DOI: 10.1016/j.antiviral.2014.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Triggering unfolded protein response by 2-Deoxy-d-glucose inhibits porcine epidemic diarrhea virus propagation

Abstract: The unfolded protein response (UPR) is cyto-protective machinery elicited towards an influx of large amount of protein synthesis in the endoplasmic reticulum (ER). Extensive studies suggest that the UPR can also be activated during virus infection. In the present studies, we first evaluated if porcine epidemic diarrhea virus (PEDV) infection activated the UPR pathways. Electron microscopy analysis demonstrated the morphology changes of ER post-PEDV infection. Western blot and real-time PCR identified the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(79 citation statements)
references
References 51 publications
4
74
1
Order By: Relevance
“…5A to I), indicating that IRE1 activation facilitates viral replication. The UPR PERK branch is highly associated with viral replication and pathogenesis (8,21,22,61). Here, we demonstrated that the TGEV-induced UPR PERK activation primarily accounted for the increased eIF2␣ phosphorylation and negatively regulated TGEV replication.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…5A to I), indicating that IRE1 activation facilitates viral replication. The UPR PERK branch is highly associated with viral replication and pathogenesis (8,21,22,61). Here, we demonstrated that the TGEV-induced UPR PERK activation primarily accounted for the increased eIF2␣ phosphorylation and negatively regulated TGEV replication.…”
Section: Discussionmentioning
confidence: 70%
“…Here, we demonstrated that the TGEV-induced UPR PERK activation primarily accounted for the increased eIF2␣ phosphorylation and negatively regulated TGEV replication. Induction of the UPR PERK has also been reported to suppress another alphacoronavirus, porcine epidemic diarrhea virus (PEDV) (61). This finding is different from the results in IBV, whose replication is not significantly affected by the suppression of eIF2␣ dephosphorylation by salubrinal (18,20).…”
Section: Discussionmentioning
confidence: 91%
“…PEDV was adapted for eight passages in Vero cells. PEDV was inactivated by UV light exposure [42]. The loss of infectivity of UV-inactivated virus was confirmed using the plaque formation assay.…”
Section: Cell and Virusmentioning
confidence: 97%
“…The infection with many CoVs induces ER stress, and a role of UPR in pathogenesis has been described (DeDiego et al, 2011). In the case of enteric porcine CoVs, the induction of the UPR response has been reported for PEDV, with a negative effect on viral replication (Wang et al, 2014b). In contrast, TGEV infection does not induce ER stress (Cruz et al, 2011), despite the increased expression of several UPR mediators such as ATF4 or GADD34 after infection [(Cruz et al, 2011), S. Zuñiga and L. Enjuanes, unpublished results].…”
Section: Host Cell Pathways Involved In Pathogenesismentioning
confidence: 98%